Accumulation of dsRNA in endosomes contributes to inefficient RNA interference in the fall armyworm, Spodoptera frugiperda. (November 2017) - Yoon, June-Sun; Gurusamy, Dhandapani; Palli, Subba Reddy
Abstract: RNA interference (RNAi) efficiency varies among insects studied. The barriers for successful RNAi include the presence of double-stranded ribonucleases (dsRNase) in the lumen and hemolymph that could potentially digest double-stranded RNA (dsRNA) and the variability in the transport of dsRNA into and within the cells. We recently showed that the dsRNAs are transported into lepidopteran cells, but they are not processed into small interference RNAs (siRNAs) because they are trapped in acidic bodies. In the current study, we focused on the identification of acidic bodies in which dsRNAs accumulate in Sf9 cells. Time-lapse imaging studies showed that dsRNAs enter Sf9 cells and accumulate in acidic bodies within 20 min after their addition to the medium. CypHer-5E-labeled dsRNA also accumulated in the midgut and fat body dissected from Spodoptera frugiperda larvae with similar patterns observed in Sf9 cells. Pharmacological inhibitor assays showed that the dsRNAs use clathrin mediated endocytosis pathway for transport into the cells. We investigated the potential dsRNA accumulation sites employing LysoTracker and double labeling experiments using the constructs to express a fusion of green fluorescence protein with early or late endosomal marker proteins and CypHer-5E-labeled dsRNA. Interestingly, CypHer-5E-labeled dsRNA accumulated predominantly in early and late endosomes. These data suggest that entrapment of internalized dsRNA in endosomes is one of the major factors contributing to inefficient RNAi response in lepidopteran insects. Graphical abstract: Highlights: dsRNAs enter Sf9 cells and accumulate in acidic bodies within 20 min of exposure. Fed/injected dsRNAs accumulate in the midgut and fat body of Spodoptera frugiperda larvae. dsRNAs use clathrin receptor-mediated endocytosis pathway for transport into the cells. dsRNAs accumulate predominantly in early and late endosomes.